Studying the Relationship between Organizational Health and Emotional Intelligence in Medical Universities of Kerman Province - RAYANI, JAMILEH; TAVAKOLI, HAMDOLLAH MANZARI; SALAJEGHEH, SANJAR; SHOKOOH, ZAHRA; MEHDIZADEH, SAMANEH (The journal of contemporary issues in business and government, 2021)
The present study aimed to investigate the relationship between organizational health and emotional intelligence in medical universities of Kerman Province. The research method is mixed-exploratory method and in terms of purpose, the research is developmental- applied which has collected data through field research. Its statistical population includes all employees of medical universities in Kerman province which are 17928 individuals that 1524 people were selected as the sample size through stratified random sampling method using Cochran's formula. Researcher-made questionnaires of organizational health and emotional intelligence were used to collect research data. Their validity was confirmed by university professors and experts and their reliability was calculated using Cronbach's alpha coefficient which was 0.706 and 0.756, respectively. The results of applying software output path analysis patterns showed the good fit of structural equation model. The results of testing the hypotheses by structural equation modeling showed that there is a direct and significant relationship between organizational health and emotional intelligence in medical universities of Kerman Province, and among the organizational health aspects, technical, administrative, and institutional levels had the most relationship with the emotional intelligence, respectively. Overall, the results indicate a significant relationship between organizational health and its dimensions with emotional intelligence. Therefore, in order to have healthy and confident people in the workplace, universities should consider emotional intelligence skills which are necessary to enjoy organizational health.